Giant mesenteric lipoma as a rare cause of ileus in a child: Report of a case - Ozel, SK; Apak, S; Ozercan, IH; Kazez, A (Springer-Verlag, 2004)
Mesenteric lipoma is a rare benign tumor of mature fat cells. Although generally asymptomatic, it occasionally causes abdominal pain, ileus, and small bowel volvulus, depending on its location and size. A definitive diagnosis can be made by pathological examination. Ultrasonography and abdominal computed tomography show this lesion as a well-defined, homogeneous mass with fat density surrounded by a thin capsule. Because of its rare etiologic origin, we report the case of a 7-year-old girl with a mass in the abdomen and ileus, found to be caused by a mesenteric lipoma.
Keywords: giant mesenteric lipoma; ileus; child